Unmet needs of parents of children with Urea Cycle disorders - Scharping, Mara; Brennenstuhl, Heiko; Garbade, Sven; Wild, Beate; Posset, Roland; Zielonka, Matthias; Kölker, Stefan; Haun, Markus W.; Opladen, Thomas (Children, 2022)
(1) Background: Phenotypic diversity and long-term health outcomes of individuals with urea cycle disorders (UCDs) have been described in detail. However, there is limited information on the burden on affected families. (2) Methods: To evaluate the family burden in parents with children suffering from UCDs, we used validated questionnaires. Socio-demographic characteristics were evaluated, and an adapted version of the Parental Need Scale for Rare Diseases questionnaire was used. The survey was conducted in families of UCD patients cared for at the University Children’s Hospital Heidelberg. (3) Results: From April to November 2021, 59 participants were interviewed (mothers n = 34, fathers n = 25). The affected patients most frequently suffered from ornithine transcarbamylase deficiency (OTC-D) (female n = 12, male n = 12), followed by argininosuccinate synthetase deficiency (ASS-D, n = 13) and argininosuccinate lyase deficiency (ASL-D, n = 8). About one-third of the participants were “dissatisfied” or “extremely dissatisfied” with health professionals’ disease knowledge. In addition, 30% of the participants reported a medium or high need for “additional information on the development of their children”, and 44% reported a medium or high need “for information on available services”. A majority of 68% reported a need for additional support regarding services such as support groups (42%) or psychological counseling (29%). (4) Conclusions: Our study indicates that there is an unmet need for sufficient information about the development of children with UCDs, as well as for information about available support services for families with UCD patients. Furthermore, the results highlight the importance of establishing or improving family-centered care approaches. This pilot study may serve as a template for the assessment of the family burden associated with other inherited metabolic diseases.
Gesehen am 10.06.2022